Screening of the process parameters for lipid production using mutant Synechococcus sp. PCC 7002 - Shari, Ummi S. Halmi; Zainal, Mus'ab; Azmi, Azlin Suhaida; Amid, Azura; Jimat, Dzun Noraini; Ahmad Raus, Raha; Muyibi, Suleyman Aremu; Mustafa, Iswaibah; Salleh, Noraini (2013)
Microalgae lipid is a promising feedstock for biodiesel production. The objective of this work was to screen growth factors affecting mutant Synechococcus sp. (PCC 7002) for high lipid production. The effect of 4 factors; nitrogen-phosporus- potassium (NPK) concentration, light intensity, temperature and NaNO3 concentration on mutant strain growth and lipid production were studied. Design Expert Version 8.0 was used to analyze data. The experimental design selected was Min-Run Res IV which consists of 12 runs and the response surfaces measured were specific growth rate and yield of lipid. The extraction of lipid was conducted by chloroform/methanol solvents system. Based on the study, mutant Synechococcus sp. (PCC 7002) gave the highest specific growth rate; 0.3811 h-1 at 0% NPK, 2500 lux, 40oC and 1% NaNO3. Besides, the highest yield of lipid was obtained at condition of 0% NPK, 3500 lux, 30oC and 1% NaNO3. It implies that, NPK did not influence both growth and lipid production of mutant strain. On the other hand, NaNO3 plays important roles in both growth and lipid production.